The Influence of Work Motivation, Work Facilities, and Job Satisfaction on Employee Work Productivity at Dinas Ketenagakerjaan Provinsi Sumatera Utara - Veronika Bangun; Ina Namora Putri Siregar; Eka Koesharni; Citra Lo Penita; Dita Eka Pertiwi Sirait (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
This study examines the influence of work motivation, work facilities, and job satisfaction on employee work productivity at the Manpower Office of North Sumatra Province. This research employed a quantitative approach. The population consisted of all employees of the Manpower Office of North Sumatra Province, totaling 139 employees, while the sample comprised 103 respondents determined using the Slovin formula. The data used in this study were primary data collected through questionnaires. The data were analyzed using multiple linear regression analysis with the assistance of SPSS version 26. The results indicate that work motivation has a significant effect on employee work productivity, work facilities have a significant effect on employee work productivity, and job satisfaction has a significant effect on employee work productivity. Simultaneously, work motivation, work facilities, and job satisfaction have a significant effect on employee work productivity at the Manpower Office of North Sumatra Province. These findings imply that improving employee productivity requires continuous efforts to enhance motivation, provide adequate work facilities, and strengthen job satisfaction within the organization.